2014
DOI: 10.1002/2013wr014722
|View full text |Cite
|
Sign up to set email alerts
|

River export of nutrients and organic matter from the North Slope of Alaska to the Beaufort Sea

Abstract: While river-borne materials are recognized as important resources supporting coastal ecosystems around the world, estimates of river export from the North Slope of Alaska have been limited by a scarcity of water chemistry and river discharge data. This paper quantifies water, nutrient, and organic matter export from the three largest rivers (Sagavanirktok, Kuparuk, and Colville) that drain Alaska's North Slope and discusses the potential importance of river inputs for biological production in coastal waters of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
131
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(144 citation statements)
references
References 70 publications
13
131
0
Order By: Relevance
“…In agreement with Frey et al [9], our results show no statistically significant difference in NO 3 between permafrost-influenced and permafrost-free watersheds although the difference in NH 4 concentration is clearly pronounced. The NO 3 and NH 4 concentrations of the WSL rivers are in general agreement with other small rivers of the permafrost zone in Alaska [26]. McClelland et al [37] reported 1.2-2.4 ppm POC in the Ob River, in fair agreement with the values 0.5-2.5 ppm in this study for WSL rivers including the Ob River middle course.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In agreement with Frey et al [9], our results show no statistically significant difference in NO 3 between permafrost-influenced and permafrost-free watersheds although the difference in NH 4 concentration is clearly pronounced. The NO 3 and NH 4 concentrations of the WSL rivers are in general agreement with other small rivers of the permafrost zone in Alaska [26]. McClelland et al [37] reported 1.2-2.4 ppm POC in the Ob River, in fair agreement with the values 0.5-2.5 ppm in this study for WSL rivers including the Ob River middle course.…”
Section: Discussionsupporting
confidence: 90%
“…Due to the high importance of the Arctic Ocean and permafrost-dominated sub-arctic continental zones in the global carbon cycle and the high vulnerability of circumpolar zones to climate warming [20][21][22], numerous studies have been devoted to the biogeochemistry of organic carbon and nutrients in large rivers of the circumpolar zone [3,[23][24][25][26][27][28][29][30]. The main source of information on long-term fluxes of dissolved and suspended material from Northern Eurasia to the Arctic Ocean is data from the Russian Hydrometeorological Survey (RHS) collected at key gauging stations of almost all major Russian Arctic rivers [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…For comparison, Holmes et al . [] reported annual DIN inputs from the Ob, Yenisey, Lena, and Kolyma of 0.18 Tg N. For N dynamics, particulate organic nitrogen (PON) also needs to be considered, as it can be much more abundant than tDON [ McClelland et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, thawing at the southern extent of permafrost may contribute to an observed latitudinal decline in NO 3 − concentration from subarctic to arctic streams [ Jones et al ., ]. Despite these general spatial and seasonal patterns linking permafrost‐driven hydrology to mobilization of C and N from catchments, significant variation in concentration or load and composition of DOM and inorganic N occurs across catchments and among regions at high latitudes [ Holmes et al ., ; McClelland et al ., ; Roth et al ., ; Tank et al ., ; Walker et al ., ].…”
Section: Introductionmentioning
confidence: 99%